PVA-TiO2 Nanocomposite Hydrogel as Immobilization Carrier for Gas-to-Liquid Wastewater Treatment - Riham Surkatti; Mark C. M. van Loosdrecht; Ibnelwaleed A. Hussein; Muftah H. El-Naas (Nanomaterials, 2024)
This study investigates the development of polyvinyl alcohol (PVA) gel matrices for biomass immobilization in wastewater treatment. The PVA hydrogels were prepared through a freezing–thawing (F-T) cross-linking process and reinforced with high surface area nanoparticles to improve their mechanical stability and porosity. The PVA/nanocomposite hydrogels were prepared using two different nanoparticle materials: iron oxide (Fe3O2) and titanium oxide (TiO2). The effects of the metal oxide nanoparticle type and content on the pore structure, hydrogel bonding, and mechanical and viscoelastic properties of the cross-linked hydrogel composites were investigated. The most durable PVA/nanoparticles matrix was then tested in the bioreactor for the biological treatment of wastewater. Morphological analysis showed that the reinforcement of PVA gel with Fe2O3 and TiO2 nanoparticles resulted in a compact nanocomposite hydrogel with regular pore distribution. The FTIR analysis highlighted the formation of bonds between nanoparticles and hydrogel, which caused more interaction within the polymeric matrix. Furthermore, the mechanical strength and Young’s modulus of the hydrogel composites were found to depend on the type and content of the nanoparticles. The most remarkable improvement in the mechanical strength of the PVA/nanoparticles composites was obtained by incorporating 0.1 wt% TiO2 and 1.0 wt% Fe2O3 nanoparticles. However, TiO2 showed more influence on the mechanical strength, with more than 900% improvement in Young’s modulus for TiO2-reinforced PVA hydrogel. Furthermore, incorporating TiO2 nanoparticles enhanced hydrogel stability but did not affect the biodegradation of organic pollutants in wastewater. These results suggest that the PVA-TiO2 hydrogel has the potential to be used as an effective carrier for biomass immobilization and wastewater treatment.